Evaluation of Suanjiangshui Quality in Different Fermentation Methods Based on Biomimetic Technology - Yao LI; Xiangcong KONG; Xingbo QU; Qiangchuan HOU; Zhuang GUO; Yurong WANG (Shipin gongye ke-ji, 2022)
In order to compare and study the quality difference of Suanjiangshui between purebred fermentation and starter fermentation, Lactobacillus fermentum pure-bred fermentation and old brine fermentation were used to make Suanjiangshui, and the sensory quality was detected by bionic equipment such as electronic tongue, electronic nose and colorimeter. The results showed that the umami of pure fermentation of Lactobacillus fermentum was obviously higher than that of fermentation with old brine, while the sourness and astringency showed opposite trend. In terms of volatile flavor, the intensity of aromatic substances in Suanjiangshui fermented by pure lactic acid bacteria was significantly higher than that fermented by starters (P<0.05). The colorimeter detection showed the brightness and greenness of pure lactic acid bacteria fermented Suanjiangshui were higher than those of starters fermented, and the color difference between them was significant (P<0.05). The results of multivariate statistical analysis indicated that there were significant differences in the overall quality of Suanjiangshui produced by different fermentation methods, and the main indicators that caused the differences were umami, aromatic and alkane volatile flavor substances. In general, the quality of Suanjiangshui fermented by pure lactic acid bacteria was better.